Peningkatan Kemampuan Operasi Hitung Nilai Uang pada Anak dengan Autisme melalui Penggunaan Aplikasi Quizizz - Silalahi, Yeni Artati; Marlina, Marlina (Pedagogi: Jurnal Ilmu Pendidikan, 2024)
Students with autism developmental challenges in communication, social interaction, and behavior due to neurological disorders. These aspects impact their understanding in classroom learning, including currency calculation proficiency. Assessment results identified two (2) eighth-grade (VIII) students with autism at SLB Doloksanggul having low currency calculation skills. This study aims to enhance teaching quality to improve these skills and assess if Quizizz application can elevate currency calculation abilities among autistic students. Subject selection involved specialized child identification tools and currency calculation assessments. The research employs a two-cycle (2) action research approach comprising planning, action, observation, and reflection. Data were collected through observation and tests. Quantitative analysis, presented via percentage graphs, and qualitative descriptions from visual data, indicated improved proficiency following Quizizz intervention. Educators are encouraged to incorporate Quizizz to enhance classroom learning quality for students with autism.